Perkembangan Pemikiran Islam dalam Menjawab Tantangan Modernitas: Penelitian - Devi Yulianti; Rina Setyaningsih; Al Azhar, Fadlan; Ashari, Hasyim; Kuswari, Hendang; Jannah, Nur; Supadi, Ari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic thought has always evolved in line with the social, political, and cultural dynamics of humanity. Modernity, with all its challenges, such as secularization, globalization, science, democracy, and human rights, demands that Islamic thought continue to engage in ijtihad and reinterpretation. This article aims to analyze the development of Islamic thought in response to modernity, both in historical and contemporary contexts. The method used is a literature review through a review of classical and modern literature. The results show that Islamic thought has undergone significant transformations, from the classical era, through the Middle Ages, to the modern era, displaying various styles: traditionalist, reformist, and neo-modernist.